Organização do Conhecimento na Ciência da Informação: uma análise métrica nos periódicos brasileiros (1972-2012) - Amorim Neto, Miguel Romeu (2013)
Investigation qualitative and quantitative analysis detecting the domain of Knowledge Organization front of the whole area of information science from surveys conducted in Referential Database Journal Articles in Information Science. The objective of the research is to analyze the occurrence numerical absolute and relative articles of Brazilian journals of information science on the topic covered in the Knowledge Organization based BRAPCI 1972-2012 through conceptual-themed cutouts. Presents concepts for understanding the Organization of Knowledge, from the approach of Domain Analysis of Hjørland and Albrechtsen (1995), which allowed them to be identified concepts of belonging OC. To meet the research objectives, we used quantitative techniques for assessing the scientific literature as a method of analyzing the data retrieved in BRAPCI and qualitative analysis. This signaled that the domain OC is expanding in Brazil unlike the international scene.